The image of copper - Sepúlveda, Marcos (Base Diseño e Innovación, 2015)
Procobre, a world leader in the promotion of copper, brings together all the stakeholders in the copper production chain, from mining to industrialization, passing through refining and smelting. The prospects for the use of copper and its social and economic importance are part of their studies and objectives.